A blind caries and fluorosis prevalence study of school-children in naturally fluoridated and nonfluoridated townships of Morayshire, Scotland - Stephen KW, Macpherson LMD, Gilmour WH, Stuart RAM, Merrett MCW. (Blackwell Synergy, 2002)
To undertake a blind caries and fluorosis prevalence study of Grade1 (aged 5/6yr) and Grade 4–7 (aged 8–12yr) children from naturally water-fluoridated (1ppm, since 1985) Burghead, Findhorn & Kinloss (F), and nearby nonfluoridated Buckie & Portessie (N-F), in rural Morayshire, Scotland.